Fish Nutrition and Feed Technology - Paolucci, Marina; Koshio, Shunsuke (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue focuses on feeding and feed technology advances and challenges in aquaculture. These are of particular interest since aquaculture and fisheries are considered crucial sources of animal protein in human diets, providing around 17% of global edible animal protein. Special attention is given to alternative sources of fish meal and how substitutions can influence the metabolism, immune response, and disease resistance of the targeted species. Moreover, the impact of plant extracts on growth performances, physiological responses, immunity, and intestinal health is addressed.